Effects of dietary chito-oligosaccharide and β-glucan on the water quality and gut microbiota, intestinal morphology, immune response, and meat quality of Chinese soft-shell turtle (Pelodiscus sinensis) - Fu, Hao; Qi, Ming; Yang, Qingman; Li, Ming; Yao, Gaohua; Bu, Weishao; Zheng, Tianlun; Pi, Xionge (Frontiers in Immunology, 2023)
Chito-oligosaccharides (COS) and β-glucan are gradually being applied in aquaculture as antioxidants and immunomodulators. However, this study examined the effects of dietary supplementation of COS and β-glucan on the water quality, gut microbiota, intestinal morphology, non-specific immunity, and meat quality of Chinese soft-shell turtle. To investigate the possible mechanisms, 3-year-old turtles were fed basal diet (CK group) and 0.1%, 0.5%, and 1% COS or β-glucan supplemented diet for 4 weeks. Colon, liver, blood and muscle tissues, colon contents, water and sediment of paddy field samples were collected and analyzed after feeding 2 and 4 weeks. The results indicated that COS and β-glucan altered microbial community composition and diversity in Chinese soft-shell turtles. The relative abundance of Cellulosilyticum, Helicobacter and Solibacillus were increased after feeding COS, while Romboutsia, Akkermansia and Paraclostridium were increased after feeding βglucan, whereas Cetobacterium, Vibrio and Edwardsiella were enriched in the control group.Furthermore, colon morphology analysis revealed that COS and β-glucan improved the length and number of intestinal villi, and the effect of 0.5 % β-glucan was more obvious. Both βglucan and COS significantly improved liver and serum lysozyme activity and antibacterial capacity. COS significantly increased the total antioxidant capacity in the liver. Further, 0.1% β-glucan significantly increased the activity of hepatic alkaline phosphatase, which closely related to the bacteria involved in lipid metabolism. Moreover, dietary supplementation with 1% COS and 1% β-glucan significantly enhanced the content of total amino acids, especially umami amino acids, in muscle tissue, with β-glucan exerting a stronger effect than COS.Additionally, these two prebiotics promoted the quality of culture water in paddy fields and reshaped the bacterial community composition of aquaculture environment. All these phenotypic changes were closely associated with the gut microbes regulated by these two prebiotics. In summary, the findings suggest that dietary supplementation with COS and βglucan in Pelodiscus sinensis could modulate the gut microbiota, improve intestinal morphology, enhance non-specific immunity and antioxidant capacity of liver and serum, increase meat quality, and improve the culture water environment. This study provides new insights and a comprehensive understanding of the positive effects of COS and ꞵ -glucan on Pelodiscus sinensis.